2015
DOI: 10.15640/rah.v4n1a7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Discovering the Self Art Therapy–Based Activity

Abstract: For immigrant students, the cultural values and norms at home and at school can vary widely. Under these conditions, it is difficult to participate in school activities because of insecurity or the fear of offending or angering others, which in turn compromises self-esteem and academic expectations. This research focused on how therapeutic art activities can help immigrant students enhance their self-identity. Therapeutic art activities can be regarded as a decolonizing medium because they are not structured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Immigrant students performing art therapy-based activities had a similar feeling. They remarked that when they earned respect from their peers, they were more likely to obtain self-esteem; they suggested that self-esteem firmly depends on the way peers see you Chen [45]. Thus, another way to see the present research model would be to consider the empathic behaviour of the therapist as a mirror that reflects the patient's trust and transforms it into self-confidence: "The therapist directs the looking; without the therapist, you might stick with what you were already thinking and a lot more can came out with the therapist's direction" Collie [65]; Patricia's narratives p 136.…”
Section: Absence Of Judgment and Congruencementioning
confidence: 99%
See 1 more Smart Citation
“…Immigrant students performing art therapy-based activities had a similar feeling. They remarked that when they earned respect from their peers, they were more likely to obtain self-esteem; they suggested that self-esteem firmly depends on the way peers see you Chen [45]. Thus, another way to see the present research model would be to consider the empathic behaviour of the therapist as a mirror that reflects the patient's trust and transforms it into self-confidence: "The therapist directs the looking; without the therapist, you might stick with what you were already thinking and a lot more can came out with the therapist's direction" Collie [65]; Patricia's narratives p 136.…”
Section: Absence Of Judgment and Congruencementioning
confidence: 99%
“…To date, art-therapy-oriented studies that have focused on the self-esteem of affected persons have shown an increase in global self-worth Chancellor et al [1,23,25,[44][45][46][47]. Trust and confidence being part of self-esteem, art therapy is helpful in building greater trust and self-disclosure Hartz et al [47] and creative processes are identified in its acts to inherently give people the authority or power to do something promoting empowerment and selfassertion Franklin [46].…”
Section: Introductionmentioning
confidence: 99%
“…Specific benefits to taking part in arts activities were also reported. Chen (2015) proposed that the act of creation supports a discovery of sense of self as it reflects the mirroring process integral to early development. Making marks on paper and creating therefore can be an affirmation of self and findings suggest that this creation helped participants express their individuality.…”
Section: Discussionmentioning
confidence: 99%
“…Specific benefits to taking part in arts activities were also reported. Chen (2015) proposed that the act of creation supports a discovery of sense of self as it reflects the mirroring process integral to early development.…”
Section: Discussionmentioning
confidence: 99%